Strategies for the enhancement of anti-cancer effect of phosphodiesterase type 5 inhibitors using drug binding fusion proteins - Kim, Hongbin; Keum, Chang Yeop; Lim, Su Yeon; Lim, Kwang Suk (Biotechnology and bioprocess engineering, 2024)
Drug repurposing is a rapidly growing for the development of new therapeutic agents. Among them, phosphodiesterase-5 (PDE5) inhibitors, which show excellent effects as a treatment for erectile dysfunction, have been continuously reported for their potential as anti-cancer agents. It is necessary to apply targeted delivery systems to enhance the efficacy of the PDE5 inhibitors (PDE5i) as anti-cancer drugs. In this study, PDE5 inhibitor-binding domain (PBD) was developed to incorporate PDE5i into antibody using biological affinity binding without any chemical modifications. The PBD spontaneously bound with PDE5i, resulting in the formation of PBD/PDE5i complex. We also constructed a recombinant fusion protein composed of an anti-HER2 scFv and PBD (HER2 scFv-PBD) to deliver the PDE5i for the treatment of HER2 positive cancer cells. HER2 scFv-PBD could deliver the PDE5i into HER2-positive cancer cells and enhanced anti-cancer effect of the PDE5i. We have demonstrated the potential of tumor-directed PDE5 inhibition as a novel form of targeted therapy using drug binding fusion proteins.